Studi Komparatif Terjemah Surah al-Mu’awwidzat: Antara Al-Qur’an dan Terjemahnya Tim Kemenag dan Al-Qur’an Tarjamah Tafsiriyah Muhammad Thalib - Baihaqi, Nurun Nisaa; Munshihah, Aty (LPPM IIQ An Nur Yogyakarta, 2022)
There are differences in the translation of Surah al-Mu'awwidzat between the translations of the Ministry of Religion Team and Muhammad Talib. The reason is that the difference occurs because of the use of different touchable methods between the two. This is important considering that the Indonesian translation of the Quran is the main reference for the general public in understanding the content of the Quran, especially Surah al-Mu'awwidzat is a letter that is widely known, memorized and studied by various groups of people in Indonesia. This research focuses on library research with a descriptive-comparative method, namely explaining the translation of Muhammad Talib and the Ministry of Religion Team in Surah al-Mu'awwidzat. Then compare the interpretations of the two by revealing the similarities, differences and the writer's criticism. The results of this study indicate (1) translation similarities have occurred between the two in QS al-Ikhlas: 1, 3 and 4, QS al-Falaq: 1 and 5 and QS. an-Nisa: 5-6; (2) the difference between the two occurs in QS al-Ikhlas in the word al-shamad, the Ministry of Religion Team translates asking for everything, while M. Talib translates Guarantee all the needs of His creatures, QS. al-Falaq in syarr, the Ministry of Religion Team translates crime while M. Talib translates bad nature and al-naffasat, the Ministry of Religion Team translates women who are sorcerers while M. Talib translates magicians. And QS an-Nisa in the word al-nisa, the Ministry of Religion Team translates humans, while M. Talib translates humans and jin; (3) M. Talib found narrow meanings and inconsistencies in translating, while the Ministry of Religion's translation team tended to be more broad and contextual in translating each vocabulary.